2001
DOI: 10.1002/jez.1035
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic and postembryonic neurogenesis in the ventral nerve cord of the freshwater crayfish Cherax destructor

Abstract: Previous studies of neurogenic activity in the thoracic neuromeres of indirect developing crustaceans indicated that the temporal patterns of neurogenesis can be correlated with the appearance of the thoracic appendages during larval and metamorphic development. To test further the idea that the temporal patterns of neurogenesis in crustaceans are related to their life histories, we examined neurogenesis in the ventral nerve cord of a direct developing crustacean, the freshwater crayfish Cherax destructor, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…By experiments using the S-phase-specifi c proliferation marker BrdU during late embryogenesis (E80 % to hatching), these authors labelled an average number of 5-6 neuroblasts per thoracic hemineuromere in a 4-h pulse of BrdU at 21 °C. Their experiments also showed that in the thoracic and pleonal ganglia, the neurogenic activity in each neuromere ceases during or before the moult to the developmental stage in which its segmental appendage is fi rst used in coordinated movements (Sullivan and Macmillan 2001 ). These results suggest that the patterns of neurogenesis in the ventral ganglia of decapod crustaceans are intimately related to the development of the segmental appendages and maturation of motor behaviours (discussed in Harzsch 2003a ).…”
Section: Development Of the Central Nervous Systemmentioning
confidence: 90%
See 3 more Smart Citations
“…By experiments using the S-phase-specifi c proliferation marker BrdU during late embryogenesis (E80 % to hatching), these authors labelled an average number of 5-6 neuroblasts per thoracic hemineuromere in a 4-h pulse of BrdU at 21 °C. Their experiments also showed that in the thoracic and pleonal ganglia, the neurogenic activity in each neuromere ceases during or before the moult to the developmental stage in which its segmental appendage is fi rst used in coordinated movements (Sullivan and Macmillan 2001 ). These results suggest that the patterns of neurogenesis in the ventral ganglia of decapod crustaceans are intimately related to the development of the segmental appendages and maturation of motor behaviours (discussed in Harzsch 2003a ).…”
Section: Development Of the Central Nervous Systemmentioning
confidence: 90%
“…The presence of segmentally arranged midline neuroblasts in the developing thoracic ganglia has been reported in several malacostracans including crayfi sh: Cherax destructor (Scholtz 1992 ;Sullivan and Macmillan 2001 ), Homarus araneus (Harzsch and Dawirs 1994 ), H. americanus (Harzsch et al 1998 ), as well as Porcellio scaber and Orchestia cavimana Scholtz 1999 , 2001 ). The cell division pattern of midline precursor cells was explored in great detail in the amphipod O. cavimana Scholtz 1999 , 2001 ; reviewed in Scholtz and Gerberding 2002 ).…”
Section: Emergence Of the Early Axonal Scaffoldmentioning
confidence: 92%
See 2 more Smart Citations
“…Neurogenesis in malacostracan crustaceans typically is driven by neuroblasts which repeatedly undergo unequal divisions to produce ganglion mother cells, which later divide again to give birth to ganglion cells (e.g. Dohle 1970Dohle , 1972Scholtz 1990Scholtz , 1992Harzsch and Dawirs 1994;Harzsch et al 1998;Gerberding and Scholtz 2001;Harzsch 2001;Sullivan and MacMillan 2001;Ungerer and Scholtz 2007;reviews Harzsch 2003a, b;Dohle et al 2004;Whitington 2004). This mode of neurogenesis in principal shares many similarities with that in insects (reviews, e.g.…”
Section: Introductionmentioning
confidence: 99%